Economic evaluation of improving HIV self-testing among MSM in China using a crowdsourced intervention: a cost-effectiveness analysis. (15th March 2023) - Ong, Jason J.; Booton, Ross D.; Tucker, Joseph D.; Tang, Weiming; Vickerman, Peter; Zhang, Lei; Mitchell, Kate M.
Abstract : Objectives: Crowdsourcing, which taps into the wisdom of crowds, has been successful in generating strategies to enhance HIV self-testing (HIVST) uptake. We determined the cost-effectiveness of a crowdsourced intervention (one-off or annual) compared with a control scenario (no crowdsourcing) among MSM living in China. Design: Economic evaluation. Methods: We used data from our cluster randomized controlled trial of MSM (NCT02796963). We used a micro-costing approach to measure direct health costs (USD2017) from a health provider perspective. Using outputs from a dynamic transmission model over a 20-year time horizon, we estimated the incremental cost-effectiveness ratios using cost per disability-adjusted life years (DALYs) averted with 3% discounting. An intervention was considered highly cost-effective if it was less than one gross domestic product (GDP, 8823) per DALY averted. Results: Across all cities, the crowdsourced intervention was highly cost-effective compared with the control scenario (incremental cost-effectiveness ratios ranged from 2263 to 6152 per DALY averted for annual crowdsourcing; 171 to 204 per DALY averted for one-off crowdsourcing). The one-off intervention was cost-saving in Guangzhou and Qingdao. Sensitivity analyses confirmed the robustness of the findings; specifically, changes in discounting, costs of the crowdsourced intervention, costs of HIV testing and cost of antiretroviral therapy did not alter our conclusions. Conclusion: Scaling up a one-off or annual crowdsourced HIV prevention intervention in four cities in China was very likely to be cost-effective. Further research is warranted to evaluate the feasibility of scaling up crowdsourced HIV prevention interventions in other settings and populations.